PENGGUNAAN REFERENSI ENDOFORA DALAM KORAN KOMPAS - Fitria, Yeni Fajar Fitria Fajar; Sinaga, Mangatur Sinaga Mangatur; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Reference is the relationship between the referent and the simbols used to represent it. Reference is outside elements language designated by the language elements. Reference endofora is that the reference to the entities contained in the text (language). Reference endofora diveded into anaphora and katafora. Anaphora refersto cross the foregoing elements, while katafora refer to cross the elements mentioned later. Reference endofora both anaphora and katafora usually use pronouns, both personal pronoun, demonstrative pronouns, and comparative pronoun. Reference endofora found in many sentences in the newspaper compass. The uniqueness of reference can be seen in terms endofora interpret. Therefore, both anaphora and katafora can be encountered in the sentences contained in the paper compass. The research is the qualitative study by the descriptive method. The research data in the form of a compass newspaper text. Then presented descriptively analysis result obtained in the study means that the data unraveled in the form of words not in the form of numbers. The results showed that the distribution of reference endofora by its nature consists of ( 1 ) the reference endofora anaphora, ( 2 ) the reference endofora katafora. Types of reference marker consisting of 1) personal pronoun references, 2) demonstrative pronoun references, 3) comparative reference pronouns. These three types of reference markers present in both anaphora and reference katafora in newspaper compass.Keyword: reference endofora, nature, type